Mechanisms controlling seasonal variations of hydrochemistry in a typical river of the Baiyangdian Basin - Xi YANG; Xiaowei JIANG; Xiaohong GENG; Rongtao MA; Taotao JI; Zhiyuan ZHANG (Shuiwen dizhi gongcheng dizhi)
To investigate the seasonal variation characteristics and controlling mechanism of the hydrochemistry of rivers that flow into the Baiyangdian Basin, the Angezhuang Reservoir—Zhongyishui River—Nanjuma River—Baigou Canal was selected to compare the hydrochemical composition of the rivers pre and post-rainy season in 2023. Various methods, including mathematical statistics, Piper diagrams, Gibbs diagrams, end-member analysis, and PHREEQC simulation, were employed. The results indicate that the hydrochemical characteristic of the Angezhuang Reservoir exhibited seasonal variation in the year 2023, which significantly influenced the hydrochemistry of the downstream river. At the confluence of the Yishui River and the Nanjuma River, the hydrochemical components were predominantly similar to those of the Yishui River, indicating that the Yishui River's flow primarily governs the mixed hydrochemistry composition of the Nanjuma River. Before and after the rainy season, due to low flow rates and weak weathering, the primary ions in the Yishui-Nanjuma River showed minimal changes with the runoff distance. During the rainy season, however, the large discharge flow from the reservoir and intense rock weathering resulted in a sharp increase in the concentration of major ions with the runoff distance. End-member analysis and PHREEQC simulation results indicated that the main hydrogeochemical processes occurring in river water during the rainy season were the dissolution/weathering of calcite, gypsum, halite, and dolomite. As a river that directly flows into Baiyangdian Basin, the hydrochemical composition of the Baigou Canal was influenced by evaporation and concentration before the rainy season, while during and after the rainy season, it was controlled by the mixing of the Nanjuma River and Baigou River. This study enhances the understanding of the mechanisms controlling river hydrochemical composition and aids in analyzing the origins of Baiyangdian Lake’s water quality.